2021
DOI: 10.1038/s41467-021-24867-2
|View full text |Cite
|
Sign up to set email alerts
|

STING suppresses bone cancer pain via immune and neuronal modulation

Abstract: Patients with advanced stage cancers frequently suffer from severe pain as a result of bone metastasis and bone destruction, for which there is no efficacious treatment. Here, using multiple mouse models of bone cancer, we report that agonists of the immune regulator STING (stimulator of interferon genes) confer remarkable protection against cancer pain, bone destruction, and local tumor burden. Repeated systemic administration of STING agonists robustly attenuates bone cancer-induced pain and improves locomot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 66 publications
3
75
1
2
Order By: Relevance
“…Chemokines and their receptors-associated neuroinflammation is essential for OIH generation ( Yang et al, 2016 ; Zhu et al, 2017 ). Wang et al (2020a) confirmed that remifentanil infusion causes mechanical allodynia and thermal hyperalgesia, along with the spinal increase in the cleavage of caspase-6, the release of CCL21 in neurons and the expression of CXCR3 in microglia. Spinal inhibition of caspase-6 activation ameliorates OIH behavior and spinal CCL21/CXCR3 accumulation.…”
Section: Caspases and Opioid-induced Hyperalgesiamentioning
confidence: 59%
See 1 more Smart Citation
“…Chemokines and their receptors-associated neuroinflammation is essential for OIH generation ( Yang et al, 2016 ; Zhu et al, 2017 ). Wang et al (2020a) confirmed that remifentanil infusion causes mechanical allodynia and thermal hyperalgesia, along with the spinal increase in the cleavage of caspase-6, the release of CCL21 in neurons and the expression of CXCR3 in microglia. Spinal inhibition of caspase-6 activation ameliorates OIH behavior and spinal CCL21/CXCR3 accumulation.…”
Section: Caspases and Opioid-induced Hyperalgesiamentioning
confidence: 59%
“…Cancer pain is also an important category of chronic pain and have the distinctive characteristic of both neuropathic pain and inflammatory pain processing ( Wang K. et al, 2020 ; Wang K. et al, 2021 ). Mounting evidence reveal that the expression of NLRP3 inflammasome, including NLRP3, apoptosis-associated speck-like protein containing a caspase activation and recruitment domain (ASC), and caspase-1, were significantly increased in a time-dependent manner in bone cancer pain ( Chen et al, 2019 ).…”
Section: Caspases and Cancer Painmentioning
confidence: 99%
“…DMXAA, also known as ASA404 or vadimezan, is a strong STING agonist without significant local or systemic toxicity and was shown to have anti-tumor immunity in mouse models. In a previous study, DMXAA showed anti-angiogenic effects [ 83 ], and recent reports found that STING activation by DMXAA reduced bone cancer pain and local tumor burden [ 84 ], and promoted CAR T cell trafficking and persistence in breast cancer [ 85 ]. Although it had various beneficial effects in preclinical models, DMXAA was ineffective when combined with platinum-based chemotherapy in a phase 3 efficacy trial in human patients with advanced non-small-cell lung cancer (NSCLC) [ 86 , 87 ].…”
Section: Sting Agonistsmentioning
confidence: 99%
“…Previous studies have correlated STING expression with elevated osteoblastic activity in a model of DNA damage-induced inflammation (DNaseII -/- , IFNR -/- ), but IL-1β, IL-6, TNF-α stimulate osteoclast differentiation, which may also explain the compromised bone quality in N153S mice ( 26 , 58 , 59 ). Of note, recent work demonstrated STING induction through DMXAA treatment in mice attenuates cancer-induced osteoclast differentiation in the femur through type I interferon signaling and that STING induction inhibited bone fracture-induced pain by suppressing nociceptor excitability ( 60 ). These results show an opposite effect of STING activation on bone cells in the femur than that observed in the vertebrae in the present study; one possible explanation for such is the impact of proinflammatory signaling in the absence of direct insult to the tissue as opposed to in the context of injury or a diseased tissue microenvironment.…”
Section: Discussionmentioning
confidence: 99%